Parametric study of a brewery effluent treatment by microalgae Scenedesmus obliquus - Teresa M. Mata (2012)
This work analyses the potential of using microalgae Scenedesmus obliquus (So) for a brewery wastewater treatment and biomass production. The chemical oxygen demand (COD), total nitrogen (TN) and total carbon (IC) was followed in time, and the influence of light exposure, light intensity and culture aeration was studied. Results show that the most adequate conditions for cultivating So in this effluent are the aerated cultures, exposed to a 12 h period of daily light, at 12000 Lux intensity. At these conditions it is obtained a maximum of 0.9 g of dry biomass per liter of culture, after 9 days, for a maximum reduction of 57.5% and 20.8% of COD and TN, respectively, after 14 days, and 56.9% of TC, after 13 days, corresponding to the final values of 1692 mg O-2/L COD, 47 mg N/L TN, and 1 mg C/L TC.